The Implementation of Family Centered Care in Postpartum Mothers - Guriti Guriti; Elsye Maria Rosa; Herlin Fitriana Kurniawati (GLOBAL HEALTH SCIENCE GROUP, 2021)
Health service is a complex social implementation because it engages in services that involve various professional groups. In realizing a healthy paradigm, health services with a family approach are developed. The family approach is an approach that empowers the potential of the family in dealing with family health problems independently by paying attention to physical, biological, social, economic and cultural aspects, especially on the health and well-being of mothers, infants, toddlers, adolescents, PUS, and the elderly. The purpose of this study was to explore the implementation of family centered care by health workers in postpartum mothers. Method: This research was a qualitative research with a case study approach. Semi-structure interview was used to interview 12 informants. Results: Based on the thematic analysis of the results of in-depth interviews and processed with NVIVO 12 Plus, 3 (three) main themes were obtained which were supported by the categories explaining the implementation of family centered care by health workers in postpartum mothers. The first theme is the responses from health workers regarding the implementation and benefits of family centered care in health services for postpartum mothers which are supported by two sub-themes, namely; (a) the form and principles of implementing family centered care by hospitals according to health workers and (b) the benefits of family centered care according to the opinion of health workers. The second theme is the opinions of patients and families about the implementation of family centered care by health workers in postpartum mothers supported by two sub-themes, namely: (a) responses and (b) the benefits of family centered care. The third theme is the obstacles to the implementation of family centered care supported by two sub-themes, namely: (a) internal barriers and (b) external impacts. Conclusions: Overall, the implementation of family centered care by health workers in postpartum mothers had a good response from health workers, the patient and the patient's family.